Acute Hyponatremia Complicated with Seizure after Adjuvant Chemotherapy with Cyclophosphamide and Epirubicin in a Breast Cancer Patient - Yun-Chu Lin; Dwan-Ying Chang (Journal of Cancer Research and Practice, 2015)
Cyclophosphamide is a widely-used alkylating agent with cytotoxic effects, as well as an immunosuppressive agent. In the past, life-threatening hyponatremia had been reported as a rare complication induced by both high-dose and low-dose cyclophosphamide. We presented a breast cancer patient who had generalized seizure after the second cycle of adjuvant cyclophosphamide plus epirubicin, as her serum sodium concentration dropped from 134 mmol/L to 115 mmol/L within one day. Complete recovery was achieved after her hyponatremia was corrected and we further successfully completed two additional cycles of cyclophosphamide. Clinicians should always keep in mind this rare but severe adverse effect of cyclophosphamide, in order to make the correct diagnosis and provide prompt medical management.